Prognostic Performance of Different Lymph Node Staging Systems in Patients With Small Bowel Neuroendocrine Tumors - Jiang, Sujing; Zhao, Lihao; Xie, Congying; Su, Huafang; Yan, Ye (Frontiers in Endocrinology, 2020)
Background The prognostic significance of the lymph node (LN) classification for small bowel neuroendocrine tumors (SBNETs) remains unknown. The aim of the present study was to evaluate and compare the prognostic assessment of different LN staging systems. Methods Patients with SBNETs were identified from the Surveillance, Epidemiology and End Results (SEER) database. The X-tile program was used to determine the cutoff value of the resected lymph nodes (RLNs), negative lymph nodes (NLNs), lymph node ratio (LNR) and the log odds of positive lymph nodes (LODDS). Survival analyses were performed using Kaplan-Meier curves with log-rank test. Logistic regression analysis was used to evaluate the differences between different periods. Univariate and multivariate Cox proportional hazards models were used to assess the prognostic value of different LN staging systems on cause-specific survival (CSS). The relative discriminative abilities of the different LN staging systems were assessed using the Akaike’s Information Criterion (AIC) and the Harrell Consistency Index (HCI). Result A total of 3680 patients were diagnosed with SBNETs between 1988 and 2014 from the SEER database. Significantly difference over time(1988-1999 vs 2000-2014) was seen in age(P<0.001), tumor differentiation(P<0.001), T stage(P<0.001) and RLNs(P<0.001) subgroups. Multivariate Cox survival analysis identified that LN status stratified by the number of RLNs, NLNs, LNR and LODDS all predicted CSS in patients with SBNETs (All P＜0.05), whereas the number of positive lymph nodes (PLNs) failed(P=0.452). When assessed using categorical variable, LODDS staging systems showed the best prognostic performance (HCI: 0.766, AIC: 7575.154) in the whole population. Further analysis based on different RLNs after eliminated the missing data showed that when the RLNs<12, the LODDS (HCI: 0.769, AIC: 1088.731) maintained the best prognostic performance as well as when the RLNs≥12(HCI: 0.835, AIC: 825.692). Among patients with LNR scores of 0 or 1, there was a residual heterogeneity of outcomes that was better stratified and characterized by the LODDS. Conclusion LODDS was a better predicator of survival when LN status was stratified as a categorical variable and should be considered when assessing the prognosis of patients with SBNETs to allow a more reliable means to stratify patient survival.